A Countermeasure of Power Attack for Lightweight Cryptographic Algorithm Using Bit Permutation Operation. Issue 1 (April 2021) - Cheng, Lifu; Zhao, Youyou; Yang, Jinjiang; Liu, Leibo
Abstract: The implantation security of cryptographic algorithm is very important. This paper proposes a method to resist power consumption attack for lightweight cryptographic algorithms. Using bit permutation operation as a countermeasure, we ensure that the position of each data of the original intermediate value data has changed after the bit is permutated, which greatly increases the difficulty of the attack. SKINNY is taken as an example for evaluate the effect of the proposed countermeasure. The experiment results show that the key will not reveal over 100, 000 energy traces by using the countermeasure.